NEUROPSYCHIATRIC AND VEGETATIVE CHANGES IN ADOLESCENT GIRLS AT RISK OF REPRODUCTIVE HEALTH DISORDERS. - Kenjayeva Dilfuza Quvvatovna; Turayev Bobir Temirpulotovich (Journal of Science in Medicine and Life, 2024)
In the context of the modern demographic crisis, the problems of reproductive health of the younger generation have become very relevant. According to many years of observations, the condition of the reproductive system of women of childbearing age worsens, and a retrospective analysis of its formation revealed a high percentage of various diseases in adulthood.